THE SECURITIZATION OF IUU FISHING IN THE SOUTHERN OCEANA SECURITIZAÇÃO DA PESCA INN NO OCEANO AUSTRAL - Ferreira, Luciano Vaz (Caderno de Relações Internacionais, 2018)
Fish stocks around the world are about to collapse, which has immensurable environmental, economic, and social consequences. Therefore, the possibility that IUU (illegal, unreported and unregulated) fishing proliferate is now followed closely by the international community. In this context, securitization processes of those issues start to arise. The Southern Ocean is particularity vulnerable to IUU fishing and may become the stage of new security dynamics.  Thus, we propose the following research question: "How is regulation of fishing at the Southern Ocean securitized and what role does international cooperation play in that process?". This article's main objective is to answer that question. Furthermore, its specific objectives are to investigate securitization of fishing internationally, to study security dynamics in the Southern Ocean, and to discuss the role of international regimes and cooperation for this process. This research project is exploratory in nature. As a research method, we applied literature review using multidisciplinary materials and document analysis.